Band edge modulated conjugated polymers for oxidation prevention - Mahale, Rajashree Y.; Arulkashmir, Arulraj; Dutta, Kingshuk; Krishnamoorthy, Kothandam (Physical Chemistry Chemical Physics, 2012)
The impact of electron transfer (ET) from a series of band edge modulated polymers to atmospheric oxygen is examined in connection with substrate oxidation prevention. Polymers with the highest occupied molecular orbital (HOMO) energy level below and above the oxygen energy level were tested and the former showed better efficiency. Furthermore, the oxidation prevention efficiency of a polymer with lower HOMO increased by two orders of magnitude, when the pores on the film were filled with spherical molecules, [6,6]-phenyl-C61-butyric acid methyl ester. We found that the polymer surface hydrophobicity has little or no influence on oxidation prevention. It is interesting to note that a polymer with a hole mobility of 8 x 10(-10) cm(2) V-1 s(-1) showed a two-fold increase in oxidation prevention efficiency compared to a polymer with a hole mobility of 6 x 10(-5) cm(2) V-1 s(-1). Over all, from the concerted approach, we conclude that a polymer devoid of pores with the HOMO energy level below oxygen and low charge carrier mobility is a suitable candidate for prevention of substrate oxidation/corrosion.

Reversible assembly and disassembly of micelles by a polymer that switches betweenhydrophilic and hydrophobic wettings - Dutta, Kingshuk; Mahale, Rajashree Y.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Langmuir, 2012)
Supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features, but the polyelectrolytes undergo conformational changes. Here we show that a charge bearing rigid conjugated polymer can alter the structural features and disassemble AAs. We also demonstrate reversible assembly and disassembly of AAs by controlling the number of charges on the rigid polymer. During the disassembly, the guest molecules sequestered in the AAs are released. The rate of release has been modulated by changing the morphology of the charge bearing polymer. Concomitant to the AAs disassembly, the polymer surface becomes hydrophobic due to the binding of the amphiphiles on the charges of the polymer backbone. By controlling the charges on the polymer, the surface wettability was varied gradually from hydrophilic to hydrophobic.

Supramolecular interaction facilitated small molecule films for organic field effect transistors - Arulkashmir, Arulraj; Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Jangid, Manoj K.; Krishnamoorthy, Kothandam (Polymer Chemistry, 2012)
Metalloporphyrins and metal free porphyrins have been explored as active materials in field effect transistors. Amorphous forms of these porphyrins are preferred over their crystalline analogue due to the ease of solution processability. To achieve solution processability, a metalloporphyrin was anchored on a vinyl polymer by taking advantage of the supramolecular interaction between the metal and the pyridine moiety of the polymer. Non covalent bonding was preferred because it provides an opportunity to better manipulate the polymer's properties compared to its covalent bonding analogue. The binding between the porphyrin and the polymer was optimised in solution and the supramolecular complex was spun on various substrates to form thin films. The porphyrin was found to be uniformly distributed throughout the polymer films contrary to the existing approaches, wherein small molecule phase segregates in the polymer film. Field effect transistors were fabricated using the porphyrin-polymer complex and the device parameters were measured at atmospheric condition. The devices annealed at 80 degrees C showed hole carrier mobility of 2.0 x 10(-4) cm(2) V-1 s(-1) with charge trapping at the dielectric semiconductor interface. Furthermore, the high carrier mobility observed at low temperature annealing makes this supramolecular complex an attractive candidate to explore in flexible substrates.

Cleavable and removable polymer thermosets for organic field effect transistor packaging - Arulkashmir, Arulraj; Bhosale, Manik E.; Krishnamoorthy, Kothandam (RSC Advances, 2013)
Recent years have witnessed tremendous progress in the design and synthesis of electroactive materials for the fabrication of organic electronic devices. However, very little research effort has been devoted to developing organic packaging materials, which are crucial for the efficient functioning of the devices. Polymer thermosets (PTs) are extensively used for the packaging of microelectronic and optoelectronic devices. Although PTs are effective in providing mechanical stability and environmental protection to devices, the removal of PTs without destroying the underlying surface is cumbersome. Facile removal of PTs is essential to reuse the expensive substrates. Herein, we report the preparation of a thermoset using an aliphatic disulfide containing cross-linker, cystamine. By varying the cross-linker concentration, the mechanical property of the thermoset was varied from ductile to brittle. The ductile thermoset was coated on metal, semiconductor and flexible substrates. The thermosets were then cleaved using a biomolecule in neutral pH. We have demonstrated that the cleavage and removal of thermosets don't affect the surface properties of the underlying substrates. Furthermore, the thermosets were coated on top of organic field effect transistors to provide environmental protection. The thermoset coated devices showed a charge carrier mobility of 5.3 x 10(-3) cm(2) V-1 s(-1). Then, the thermoset was cleaved and removed, and the substrate was reused for the fabrication of organic field effect transistors with unchanged device efficiencies.

Enhanced hole carrier transport due to increased intermolecular contacts in small molecule based field effect transistors - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Das, Chayanika; Muddellu, Pooja; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2013)
Small molecules and oligomers can be synthesized with very high purity and precise molecular weights, but they often do not form uniform thin films while processed from solution. Decreased intermolecular contacts between the small molecules are another disadvantage. To increase the intermolecular contacts in small molecules, we have chosen i-indigo, as one of the conjugated molecular units. The electron poor i-indigo has been connected with electron rich triphenylamine to synthesize a donor-acceptor-donor type small molecule. The propeller shaped triphenylamine helps to increase the solubility of the small molecule as well as isotropic charge transport. The intermolecular spacing between the molecules has been found to be low and did not vary as a function of thermal annealing. This implies that the intermolecular contacts between the small molecules are enhanced, and they do not vary as a function of thermal annealing. Organic field effect transistors (OFET) fabricated using a small molecule exhibited a hole carrier mobility (mu) of 0.3 cm(2)/(V s) before thermal annealing. A marginal increase in mu was observed upon thermal annealing at 150 degrees C, which has been attributed to changes in thin film morphology. The morphology of the thin films plays an important role in charge transport in addition to the intermolecular spacing that can be modulated with a judicious choice of the conjugated molecular unit.
Keywords: hole mobility; i-indigo; organic field effect transistor; quadrupole interaction; small molecules; triphenylamine

Chemically doped perylene diimide lamellae based field effect transistor with low operating voltage and high charge carrier mobility - Arulkashmir, Arulraj; Jain, Bhanprakash; John, Jino C.; Roy, Kanak; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Chemical doping of an electron transporter results in the formation of a radical anion containing semiconductor which showed high electron mobility (13 cm(2) V-1 s(-1)) at low operating voltage (1 V).

Disassembly of micelles in nanoscopic space to prepare concentric nanotubes with variable hydrophobic interiors - Das, Chayanika; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Nanotubes with variable hydrophobic interiors were prepared by disassembling anionic micelles in the inner walls of positive charge bearing conjugated polymer nanotubes.

Organic soluble and uniform film forming oligoethylene glycol substituted BODIPY small molecules with improved hole mobility - Singh, Saumya; Venugopalan, Vijay; Krishnamoorthy, Kothandam (Physical Chemistry Chemical Physics, 2014)
Judiciously chosen side chains of conjugated molecules have a positive impact on charge transport properties when used as the active material in organic electronic devices. Amongst the side chains, oligoethylene glycols (OEGs) have been relatively unexplored due to their hydrophilic nature. OEGs also affect the smooth film formation of conjugated molecules, which preclude device fabrication. However, X-ray diffraction studies have shown that OEGs facilitate intermolecular contact, which is a desirable property for the fabrication of organic electronic devices. Thus the challenge is to design and synthesize organic solvent soluble and uniform film forming conjugated molecules with OEG side chains. We have designed and synthesized conjugated small molecules (CSMs) comprising BODIPY as acceptor and triphenylamine as donor with an OEG side chain. This molecule forms smooth films when processed from organic solvents. In order to understand the impact of the OEG side chain, we have also synthesized alkyl chain analogs. All the molecules exhibit exactly the same HOMO and LUMO energy levels, but the packing in the solid state is different. CSM with methyl side chains exhibit an inter planar distance of 4.15 A. Contrary to this, the OEG side chain containing CSM showed an inter planar spacing of 4.30 A, which is 0.2 A less than the alkyl side chain comprising CSMs. Please note that the length of the hydrophobic and hydrophilic side chains is the same. Interestingly, the OEG side chain comprising CSM showed two orders of higher hole carrier mobilities compared to all the other derivatives. The same molecule also showed an extremely low threshold voltage of -0.27 V indicating the OEG side chains' favourable interaction between substrate as well as between molecules.

pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Chemically reduced organic small-molecule-based lithium battery with improved efficiency - Bhosale, Manik E.; Krishnamoorthy, Kothandam (Chemistry of Materials, 2015)
Organic lithium batteries are attractive because of the possibility of fabricating lightweight and flexible devices. However, the organic lithium batteries have a few drawbacks. The specific capacity is usually lower than the theoretical capacity, which further decreases upon cycling. Often, the specific capacity is very low compared to theoretical capacity while discharging the battery at moderate and high C rates. To circumvent this issue, we chemically reduced carboxylic acid functionality substituted perylene diimide (benzoic-PDI) with hydrazine. Indeed, we found that the rate of redox reaction as well as the conductivity of the benzoic-PDI increased upon chemical reduction. The battery comprising reduced benzoic-PDI exhibits 100% Coulombic efficiency and specific capacity while discharging at 20C. The battery also exhibits very high specific energy (213 Wh/kg) and specific power (8548 W/kg). The control experiments confirm our hypothesis of using chemical reduction to improve the performance of organic lithium battery.

Phenols from green tea as a dual functional coating to prepare devices for energy storage and molecular separation - Das, Chayanika; Jain, Bhanprakash; Krishnamoorthy, Kothandam (Chemical Communications, 2015)
Polyphenols from green tea were used to electrolessly deposit gold on silk cocoons (SCs) and nanoporous aluminum oxide (AAO) templates. The gold coated cocoons were used as electrodes in supercapacitors and showed a capacitance as high as 254 F g(-1) and a specific power of 2287 W kg(-1). A metal coated AAO template was used for molecular separation.

Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Synthesis, optoelectronic, and transistor properties of BODIPY- and cyclopenta[c]thiophene-containing pi-conjugated copolymers - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Physical Chemistry C, 2015)
Three new low-band-gap copolymers were synthesized by fusing dipyrromethene difluoroborane (BODIPY) as the acceptor (A) and thiophene-capped 5,5-bis(hexyloxymethyl)-5,6-dihydro-4H-cyclopenta[c]-thiophene (CPT) as the donor (D). The BODIPY unit was copolymerized through the `alpha' positions (1 and 7 positions) in P1 and through the `beta' positions (2 and 6 positions) in P2 and P3. The additional acetylene unit between D and A in P3 enhanced the conjugation by minimizing the possible steric hindrance compared to that in P2, whereas P1 exhibited a more red-shifted absorption than P2 and P3 because of the more effective conjugaion through the `alpha' positions of BODIPY. Importantly, the optical band gaps (E-g(opt)) obtained from the onset of the absorption spectra are 1.28, 1.71, and 1.57 eV for P1, P2, and P3, respectively. P1 has the lowest band gap for any CPT-containing polymer. In the best transistor devices, a mobility improvement by 4 orders of magnitude from 3.22 x 10(-6) cm(2) V-1 s(-1) for P2 to 0.01 cm(2) V-1 s(-1) for P1 was achieved. DFT calculations alongside measured charge-transport properties indicated that appreciable alterations in the optoelectronic properties of the polymers were achieved through minor changes in their structural features. The polymers were further characterized by thin-film X-ray diffraction, atomic force microscopy, and spectroelectrochemistry to investigate their material and electrochemical properties.

Alkyl-chain-separated triphenybenzene - carbazole conjugates and their derived polymers: candidates for sensory, electrical and optical materials - Kaleeswaran, D.; Vishnoi, Pratap; Kumar, Subramani; Chithiravel, Sundaresan; Walawalkar, Mrinalini G.; Krishnamoorthy, Kothandam; Murugavel, Ramaswamy (Chemistry Select, 2016)
Four new triphenylbenzene based carbazoles (THPBCz4, THPBCz6, THPBCz8 and THPBCz10) and polycarbazoles (polyTHPBCz4, polyTHPBCz6, polyTHPBCz8 and polyTHPBCz10), have been synthesized. Photoluminescence spectra of the monomers in dichloromethane exhibit two intense bands at 353 and 369 nm. Two additional bands (410 and 435 nm) are also observed due to intermolecular interactions. These bands are more intense in the case of thin films, indicating stronger pp stacking interactions in the solid state. Due to the extended p-conjugation, the polycarbazoles display two main emission bands (495 and 520 nm) which are red shifted as compared to the monocarbazoles. Due to the presence of emissive platforms such as triarylbenzene and carbazole, both monomers and polymers, function as efficient sensors for the detection of polynitroaromatic analytes (PA, DNT, rho-DNB and m-DNB). The electrochemically polymerized carbazole derivatives showed maximum capacitance of 41 F/g for polyTHPBCz6. The SCLC measurement reveals a maximum mobility of 6 x 10(-6) cm(2)/Vs for polyTHPBCz4 that showed better packing due to flexible alkyl chains that connect the conjugated moieties.

Band edge modulated polymer layer to decrease back electron transfer and increase efficiency in sensitized solar cells - Arulkashmir, Arulraj; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Advanced Energy Materials, 2016)
Recombination of charges residing in the TiO2 and redox electrolyte is one of the factors affecting the efficiency of dye sensitized solar cells (DSSCs). To circumvent this recombination, inorganic oxide barrier layers and organic silanes have been coated on TiO2/dyes. Due to the insulating nature of these layers, the efficiency increase is not very impressive. Conducting polymers with different band edges are used to suppress the charge recombination. Amongst the four polymers that are used as barrier layers, a polymer with a highest occupied molecular orbital energy at -5.8 eV and lowest unoccupied molecular orbital at -3.1 eV is found to increase the electron life time at TiO2 and decrease the charge recombination. The electron life time is found to be 88 ms. In addition to the long electron life time, the recombination resistance of this polymer is also high (91 Omega). This resistance is 18% higher than that measured for DSSCs without polymer barrier layer. These factors impact the efficiency of DSSCs. DSSCs fabricated with this polymer as barrier layer exhibit an efficiency of 9.2%, which is 22% higher than that of DSSCs without polymer barrier layer.

"Click" polymerization: a convenient strategy to prepare designer fullerene materials - Krishnamurthy, Munusamy; Krishnamoorthy, Kothandam; Arulkashmir, Arulraj; Raghavendra, V.; Murali, Adhigan; Jaisankar, Sellamuthu N.; Murugan, P.; Gurusamy-Thangavelu, Senthil A.; Nasar, A. Sultan; Mandal, Asit Baran; Samanta, Debasis (Materials & Design, 2016)
"Click" polymeric assemblies of fullerenes, thiophenes and aryl compounds were prepared for the first time to study their spectroscopic/chemical/electronic characteristics and possible applications in photovoltaic cells. The GPC and NMR spectroscopic data confirmed a moderate to high degree of polymerization while microscopic pictures showed well-defined arrangements of fullerenes. The FTIR studies indicated that the product is free from starting azide materials, whereas thermogravimetric analysis data suggested a good stability. Band gap of the material was determined using UV-Vis spectroscopy, cyclic voltammetric techniques and compared with computational investigation. The fullerene copolymer was fabricated as acceptor material in a bulk heterojunction photovoltaic cell. (C) 2016 Elsevier Ltd. All rights reserved.

Conjugated porous polymers as precursors for electrocatalysts and storage electrode materials - Bhosale, Manik E.; Illathvalappil, Rajith; Kurungot, Sreekumar; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
Conjugated porous polymers were used as precursors to prepare nitrogen and sulphur doped carbon atoms, which were then used for oxygen reduction and energy storage.

Copolymers comprising monomers with various dipole and quadrupole as active material in organic field effect transistors - Singh, Saumya; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam (Journal of Physical Chemistry C, 2016)
Copolymers of 4,4-difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) and diketopyrrolopyrrole (DPP) were synthesized. The BODIPY has a permanent dipole and the DPP has a quadrupole. The dipole and the quadrupole in the monomers are expected to bring the polymers closer and to improve the charge-transport properties. By judicious choice of these monomers, the electron wave function is evenly distributed through the molecules. However, we notice that the torsional angle at the connecting point of BODIPY and DPP is a function of the methyl moieties at the beta,beta' position of the BODIPY. We found that the polymer comprising DPP and BODIPY without methyl moiety at beta,beta' position showed a torsional angle of 27, the lowest among the three polymers studied in this work. The absorption spectrum of the polymer showed transitions because of vibronic coupling indicating linearity along the polymer backbone. The band gap of the polymer was found to be 1.2 eV. The thermally stable polymer showed an ambipolar charge transport of 0.01 cm(2)/(V s).

Disassembly of micelles to impart donor and acceptor gradation to enhance organic solar cell efficiency - Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2016)
A transparent, conducting and low surface energy surface was prepared by disassembly of anionic micelles, which altered the orientation of the donor polymer and imparted gradation between the donor and acceptor. This configuration increased the solar cell device efficiency.

Flexible microsupercapacitors using silk and cotton substrates - Das, Chayanika; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2016)
Flexible microsupercapacitors (MSCs) are needed to power ultrasmall wearable electronic devices. Silk cocoons comprise microfibers of silk, which is an attractive natural resource to fabricate MSCs. These fibers are insulators; hence, they must be converted to conducting surfaces. Polyphenols from green tea have been used as a protective layer that also acted as a reducing agent for silver ions. The reduction of silver ions resulted in the formation of silver nanoparticles that subsequently reduced gold ions to gold. The gold film imparts conductivity to the silk fiber without affecting the mechanical strength of the silk fiber. The mechanical strength of uncoated silk fiber and gold coated silk fiber were found to be 5.2 and 5 GPa, respectively. A pseudocapacitive polymer, poly(3,4-ethylenedioxythiophene), was used as the active material to fabricate MSCs. The MSCs showed an impressive gravimetric capacitance of 500 F/g and areal capacitance of 62 mF/cm(2). The power and energy densities were calculated to be 2458 W/kg and 44 Wh/kg, respectively. The device was coiled on a cylinder, and the performance of the device was found to be same as that of the uncoiled device. To demonstrate that the approach is not specific to silk, we also coated gold on cotton fibers using the protocol used to coat gold on silk. Coiled and uncoiled supercapacitors were fabricated using PEDOT coated cotton fibers. The gravimetric capacitance was found to be 250 F/g with energy and power densities of 5.5 Wh/kg and 1118 W/kg, respectively. We have also demonstrated that the devices can be connected in parallel and series to improve the performance of the miniaturized devices.

Selenium-containing fused bicyclic heterocycle diselenolodiselenole: field effect transistorstudy and structure property relationship - Debnath, Sashi; Chithiravel, Sundaresan; Sharma, Sagar; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (ACS Applied Materials & Interfaces, 2016)
The first application of the diselenolodiselenole (C4Se4) heterocycle as an active organic field effect transistor materials is demonstrated here. C4Se4 derivatives (2a-2d) were obtained by using a newly developed straightforward diselenocyclization protocol, which includes the reaction of diynes with selenium powder at elevated temperature. C4Se4 derivatives exhibit strong donor characteristics and planar structure (except 2d). The atomic force microscopic analysis and thin-film X-ray diffraction pattern of compounds 2a-2d indicated the formation of distinct crystalline films that contain large domains. A scanning electron microscopy study of compound 2b showed development of symmetrical grains with an average diameter of 150 nm. Interestingly, 2b exhibited superior hole mobility, approaching 0.027 cm(2) V-1 s(-1) with a transconductance of 9.2 mu S. This study correlate the effect of p-stacking, Se center dot center dot center dot Se intermolecular interaction, and planarity with the charge transport properties and performance in the field effect transistor devices. We have shown that the planarity in C4Se4 derivatives was achieved by varying the end groups attached to the C4Se4 core. In turn, optoelectronic properties can also be tuned for all these derivatives by end-group variation.

Site-selective synthesis and characterization of BODIPY-acetylene copolymers and their transistor properties - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
To study the effect of site-selective copolymerization of borondipyrromethene (BODIPY) with acetylene on the structural and optoelectronic properties, three copolymers P1-P3 were synthesized by the Sonogashira cross-coupling of BODIPY units with diacetylene and bromine capping through all the possible linkages: alpha-alpha (P1), alpha-beta (P2), and beta-beta (P3). The optoelectronic properties of the polymers were investigated systematically to understand the effect of site-selective polymerization. The HOMO levels of the polymers were significantly tuned from P1 to P3 with negligible change in the LUMO levels. Broadening of absorption spectra from P3 to P1 was observed because of increase in the extent of conjugation. Additionally, the charge transport properties of these polymers in organic thin-film transistors (OTFTs) revealed that P1 and P3 exhibited only p-type mobility, whereas P2 exhibited electron mobility. Notably, the further investigations of the surface morphology of polymer films by atomic force microscopy (AFM) unveiled that comb like nanostructural arrangements in P3 was beneficial for the charge-carrier mobility over the circular arrangements in P1 and P2. (C) 2016 Wiley Periodicals, Inc.
Keywords: acetylene; BODIPY; DFT; low-band gap

Synthesis and characterization of simple cost-effective trans-A(2)BC porphyrins with various donor groups for dye-sensitized solar cells - Kumar, Ravi; Sankar, Muniappan; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (New Journal of Chemistry, 2016)
We have designed and synthesized a series of simple cost-effective 'push-pull' Zn(II) porphyrin dyes containing various electron donors such as 2-thienyl, pyrenyl, phenyl, 4'-bromophenyl, 4'-tbutylphenyl and 4'-carboxyphenyl acceptor moieties in three steps. Their optical absorption spectra, electrochemical redox and photovoltaic properties have been investigated in detail. The overall power conversion efficiencies (Z) of DSSCs based on these dyes are in the range of 2.1 to 4.2% and highly depend on their donor moiety. The incorporation of trans-10,20-dimesityl groups is highly beneficial for preventing the p-p aggregation among the porphyrin moieties, thus favorably suppressing the charge recombination and intermolecular interaction. Among all, pyrenyl appended Zn(II) porphyrin has exhibited a higher power conversion efficiency of 4.2% under 1 sun illumination due to the extended p-conjugation and electron donating ability of the pyrenyl moiety.

Fabrication, characterization and comparison of DSSC using anatase TiO 2 synthesized by various methods - Umale, Sanjivani V.; Tambat, Sneha N.; Vediappan, Sudhakar; Sontakke, Sharad M.; Krishnamoorthy, Kothandam (Advanced Powder Technology, 2017)
In this study, anatase TiO2 nanoparticles were synthesized by three techniques, namely, sol-gel, acid-base co-catalyst and room temperature colloidal methods. The synthesized materials were characterized by X-ray diffraction, scanning electron microscopy, pore diameter, pore volume and surface area. The dye-sensitized solar cells were fabricated using the synthesized materials and characterized for incident photon to current conversion efficiency, photocurrent density to photo voltage measurement and electrochemical impedance analysis. Among the studied materials, TiO2 synthesized by sol-gel method displayed highest photon to current conversion of 76.8% and a maximum solar cell efficiency of 7.85% with Jsc of 14.75mA/cm², Voc of 0.76V and FF of 0.7. This is the first study to report a high power conversion efficiency of DSSC using a sol-gel synthesized titania and its comparison with other two synthesized materials. The high power conversion efficiency of the solar cell using TiO2 synthesized by sol-gel method is attributed to its characteristic properties such high surface area, larger pore diameter and larger pore volume and highest dye loading capacity.

Heteroatom facilitated preparation of electrodes for sodium ion batteries - Bhosale, Manik E.; Banerjee, Abhik; Krishnamoorthy, Kothandam (RSC Advances, 2017)
A conjugated polymer comprising heterocycles was prepared and carbonized to obtain carbon with interlayer spacings between 0.42 and 0.37 nm and exhibited a specific capacity of 250 mA h g(-1).

Increasing light coupling in a photovoltaic film by tuning nanoparticle shape with substrate surface energy - Kataria, Devika; Krishnamoorthy, Kothandam; Iyer, S. Sundar Kumar (Materials Research Express, 2017)
Tuning metal nanoparticle (MNP) contact angle on the surface it is formed can help maximise the useful optical coupling in photovoltaic films by localized surface plasmon (LSP) resonance-opening up the possibility of building improved photovoltaic cells. In this work experimental demonstration of optical absorption increase in copper phthalocyanine (CuPc) films by tuning silver MNP shape by changing its contact angles with substrate has been reported. Thin films of poly3,4 ethylenedioxythiophene: sodium dodecycl sulphate (PEDOT: SDS) with different surface energies were formed on indium tin oxide (ITO) coated glass by electro-deposition. Silver MNPs thermally evaporated directly on ozonised ITO as well as on the PEDOT: SDS films showed contact angles ranging from 60 degrees to 125 degrees. The CuPc layer was deposited on top of the MNPs. For the samples studied, best optical absorption in the CuPc layer was for a contact angle of 110 degrees.

Polymer and graphene layer to increase dye regeneration and suppress back electron transfer in dye sensitized solar cells - Sudhakar, Vediappan; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2017)
Dye regeneration was improved by using an optimum quantity of graphene, which was dispersed in a polymer that suppresses back electron transfer. Using this approach, DSSCs with an efficiency of 10.4% have been fabricated.

Self-assembled spheres, flowers, and fibers from the same backbone and similar side chains - Singh, Anup Kumar; Krishnamoorthy, Kothandam (Langmuir, 2017)
Rylene imides (Ms) self-assemble into various nanostructures. Often, the synthesis of unsymmetrical RIs (URIs) is required to achieve nanostructures. However, the synthesis of URIs is nontrivial. Thus, a structurally similar alternative is desirable. iso-Indigo (i-indigo) has a pi core and lactam rings that are structurally similar to the RIs. Unsymmetrical iso-indigo (i-indigo) can be easily synthesized by condensing oxindole and isatin. We have synthesized a series of unsymmetrical i-indigo molecules. In these molecules, the pi-pi interaction, hydrogen bonding, and van der Waals interactions are in operation. Because of these, the molecules self-assemble into spheres, fibers, and dahlia flower morphologies. If the hydrogen bonding interaction is disrupted, then all of them form fibers. Control experiments indicate that the complete absence of hydrogen bonding is deleterious to self-assembly. We also show that the lower analogs of i-indigo are not sufficient to form self-assembled nanostructures.

Dihedral angle control to improve the charge transport properties of conjugated polymers in organic field effect transistors - Dharmapurikar, Satej S.; Chithiravel, Sundaresan; Mane, Manoj V.; Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Chemical Physics Letters, 2018)
Diketopyrrolopyrrole (DPP) and i-Indigo (i-Ind) are two monomers that are widely explored as active materials in organic field effect transistor and solar cells. These two molecules showed impressive charge carrier mobility due to better packing that are facilitated by quadrupoles. We hypothesized that the copolymers of these monomers would also exhibit high charge carrier mobility. However, we envisioned that the dihedral angle at the connecting point between the monomers will play a crucial role in packing as well as charge transport. To understand the impact of dihedral angle on charge transport, we synthesized three copolymers, wherein the DPP was sandwiched between benzenes, thiophenes and furans. The copolymer of i-Indigo and furan comprising DPP showed a band gap of 1.4 eV with a very high dihedral angle of 179 degrees. The polymer was found to pack better and the coherence length was found to be 112 angstrom. The hole carrier mobility of these polymer was found to be highest among the synthesized polymer i. e. 0.01 cm(2)/vs. The copolymer comprising benzene did not transport hole and electrons. The dihedral angle at the connecting point between i and Indigo and benzene DPP was 143 angstrom, which the packing and consequently charge transport properties. (C) 2018 Elsevier B. V. All rights reserved.

Experimental and theoretical investigations of different diketopyrrolopyrrole-based polymers - Murugan, Pachaiyappan; Raghavendra, Venkatraman.; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Mandal, Asit Baran; Subramanian, Venkatesan; Samanta, Debasis (ACS Omega, 2018)
Diketopyrrolopyrrole (DPP)-based polymers are often considered las the most promising donor moiety in traditional bulk heterojunction solar cell devices. In this paper, we report the synthesis, characterization of various DPP-based copolymers with different molecular weights, l and polydisper sity where other aromatic repeating units (phenyl or thiophene based) are connected by alternate double bonds or triple bonds. Some of the copolymers were used for device fabrication and the crucial parameters such as fill factor (FF) and open circuit voltage (V-oc) were calculated. The density functional theory was used to optimize the geometries and deduce highest occupied molecular orbital lowest unoccupied molecular orbital gaps of all the polymers and'theoretically predict their optical and electronic properties. Optical properties of all the polymers, electrochemical properties and band gaps were also obtained experimentally and compared with the theoretically predicted values.

Modulated photochemical reactivities of O-acetylated (3', 5'-dimethoxyphenyl) heteroaryl acyloin derivatives under direct irradiation and photo-induced electron transfer conditions - Bisht, Rajesh; Singh, Saumya; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemical & Photobiological Sciences, 2018)
3', 5'-Dimethoxybenzoin esters are important photoremovable protecting groups which form 2-phenylbenzofuran derivatives upon photo-release. We utilized a similar concept to test a photochemical method of installing a benzofuran moiety to the conjugated backbone by subjecting O-acetylated (3', 5'-dimethylphenyl) heteroaryl acyloin derivatives through direct photo irradiation and a photo-induced electron transfer reaction. These photochemical methods were explored for a variety of heteroaromatic substrates appended on the ketone part of the O-acetylated cross-acyloin derivatives. The furan, thiophene and bithiophene derivatives led to the expected cyclized (benzofuran capped) products but the derivatives with extended conjugation decomposed under direct irradiation. However, under irradiation in the presence of an electron donor such as triethylamine, the extended acyloin derivatives afforded both cyclized and deacetoxylated products. The semiconducting nature of the extended cyclized products was also explored and tested for solution-processed organic field effect transistors, providing a maximum hole mobility of 1.3 x 10(-6) cm(2) V-1 s(-1).

Silk cocoon as counter - electrode substrate in dye - sensitized solar cells - Sudhakar, Vediappan; Das, Chayanika; Krishnamoorthy, Kothandam (ChemistrySelect, 2018)
Electrodes are vital components of energy conversion devices such as dye sensitized solar cells (DSSCs). The widely used electrodes consist of fluorine doped tin oxide (FTO) and platinum. We were interested in identifying a substrate that is available from natural resources and exhibit performance comparable to that of Pt coated FTO (Pt-FTO). Silk fibers are naturally available and they are mechanically stable. The woven silk fibers are known as silk cocoons (SCs) that structurally resemble widely used carbon paper electrodes. To impart conductivity to the insulating SCs, metal film was coated by an electroless metal plating procedure using polyphenols from green tea. The metal coated SCs were conformaly coated with a conjugated polymer and these electrodes were used as flexible electrodes in DSSCs. The flexible electrode based DSSCs exhibited a power conversion efficiency of 7.2% which is comparable to that of the DSSCs with rigid Pt-FTO based devices (7.4%).
Keywords: counter electrode; PEDOT-G-SCs; Recombination; Silk cocoons (SCs)

Conversion of curved assemblies into two dimensional sheets - Deshmukh, Gunvant; Krishnamoorthy, Kothandam (Nanoscale, 2019)
The design and preparation of organic two dimensional (O2D) sheets and their conversion to curved nanostructures is in its infancy. To convert a flat structure into a curved structure, the molecule must have multiple interaction possibilities and an in-built twist. The conjugated small molecule iso-Indigo (i-Indigo) comprises two phenyl rings that are twisted (the dihedral angle is 15 degrees) at the junction. The i-Indigo has been connected with moieties that impart hydrogen bonding and van der Waals interactions. Due to the presence of the cloud in i-Indigo, - interactions are also present in the molecule. While all three interactions are in operation, rings and toroids are formed. Upon addition of hydrogen bonding competing solvents, the rings and toroids unravel to form O2D sheets. Control molecules that don't have hydrogen bonding moieties and - interactions form random assemblies. Please note that the rings, toroids and O2D sheets are formed in a single solvent by simple dissolution, unlike previous approaches that involve multiple steps and solvents.

Enhancing the device efficiency by filling the traps in photoanodes - Sudhakar, Vediappan; Krishnamoorthy, Kothandam (Journal of Materials Chemistry C, 2019)
Traps are ubiquitous in semiconductors and act as recombination sites. These recombination sites have a deleterious effect on the device efficiency. Thus, trap filling is used to increase the efficiency of devices. The traps are filled by dopants that either inject or extract electrons to/from the semiconductor. The trap-filled devices exhibit superior performance as compared to their unfilled counterparts. However, to date, this approach has not been explored in dye-sensitized solar cells despite the well-established presence of traps in them. The traps in the TiO2 photoanode are due to the presence of oxygen vacancies. Therefore, herein, we treated the photo anodes with hydrazine and filled the traps that increased all device metrics. Moreover, further sintering of the trap-filled photoanodes in the presence of hydrazine led to the formation of a nitrogen-doped photoanode. The device comprising a nitrogen-doped photoanode exhibited the efficiency increase of 23%. The detailed analysis of the device performance led to the conclusion that trap filling suppressed back electron transfer and increased the photo conversion efficiency.

Evolution of ZnO nanostructures as hexagonal disk: Implementation as photoanode material and efficiency enhancement in Al: ZnO based dye sensitized solar cells - Parra, Mohammad Ramzan; Pandey, Padmini; Siddiqui, Hafsa; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Haque, Fozia Z. (Applied Surface Science, 2019)
Hexagon shaped pristine and Al doped ZnO nanodisks (NDs) with exposed +/- [0001] polar facets were successfully synthesized using modified sol-gel method without the involvement of any structural directing or capping agents. It was investigated that OH- ions in mixed solvent system is responsible for pore formation and inhibit the growth of ZnO along the direction of c-axis leading to a high percentage exposure of active +/- [0001] polar facets and encourage the formation of ZnO NDs. Crystallographic analysis revealed that crystallite size and lattice constants are decreased, with the addition of Al3+ ions. The results obtained from Raman, and XPS analysis further corroborated with the XRD results, revealed the successful incorporation of Al3+ ions into ZnO lattice. Optical study revealed the band gap tunability with the incorporation of Al ion as dopant. Enhanced power conversion efficiency (PCE) of 1.96% (J(sc) similar to 7.69 +/- 0.23 mA/cm(2)) was observed for Al: ZnO hexagonal NDs based DSSC. The increased PCE in Al: ZnO based DSSC can be attributed to the higher inner surface area for dye anchoring by the interconnected network of the disk-like structure. The obtained results were satisfactory and most importantly the synthesis procedure proposed in present work is excellent for the synthesis of perfectly hexagonal shaped disks under precised synthesis parameters. The device interface study was further conducted using electrochemical impedance spectroscopy which revealed better charge transport process and charge storage ability with the incorporation of Al3+ ions into ZnO lattice.
Keywords: dye sensitized solar cells; Hexagonal disks; Sol-gel method; ZnO

Trans-A(2)B(2) Zn(II) porphyrin dyes with various donor groups and their Co-sensitization for highly efficient dye-sensitized solar cells - Prakash, Kamal; Sudhakar, Vediappan; Sankar, Muniappan; Krishnamoorthy, Kothandam (Dyes and Pigments, 2019)
{We have designed and synthesized four donor-acceptor based trans-A(2)B(2) Zn(II) porphyrin dyes with various donor moieties and phenylcarboxy as acceptor group in three steps. Two strong electron-donating groups (carbazole, phenothiazine, pyrene and bisthiophene) were attached to porphyrin core to enhance the light absorption of dye molecules and phenylcarboxy acted as acceptor group on TiO2 surface. The alkyl chains present in KP-Zn-CBZ and KP-Zn-PTZ dyes are helpful to suppress the aggregation of dyes at the semiconductor surface. The synthetic route of these dyes was facile, high yield and three steps procedure which involved MacDonald condensation followed by hydrolysis and Zn insertion. The absorption and emission bands of all four dyes were broadened and red shifted due to the charge transfer from donor groups to porphyrin moiety. A wide range of power conversion efficiency was shown by dyes and the order of eta was as followed KP-Zn-PTZ (5.48%) > KP-Zn-PYR (3.38%) > KP-Zn-CBZ (2.64%) > KP-Zn-BTP (1.71%). Co-sensitization of porphyrin dyes with N719 dye promoted the complementary absorption in the visible region and put a restriction on dye aggregation also which improved the cell performance. Co-sensitized KP-Zn-PTZ with N719 dye showed the highest PCE efficiency up to 8.80% with a J(SC) = 17.4 mA cm(-2)

Aromatic amine passivated TiO2 for dye-sensitized solar cells (DSSC) with similar to 9.8% efficiency - Kumar, T. R. Naveen; Yuvaraj, S.; Kavitha, P.; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Neppolian, B. (Solar Energy, 2020)
In this work, the efficiency of dye-sensitized solar cells (DSSC) was improved by capping TiO2 with simple aromatic amines as a complexing agent. The aromatic amines, aniline and o-phenylenediamine capped TiO2 composites were synthesized via hydrothermal route and used as scattering layer in dye-sensitized solar cell (DSSC). Markedly, the maximum photo-conversion efficiency of 9.84% was achieved with o-phenylenediamine capped-TiO2 composite as o-phenylenediamine capped-TiO2 showed higher reflectivity than the pristine TiO2, which is highly beneficial for reflecting the photons back to photoanode. In addition, the average life time of carriers in o-phenylenediamine capped-TiO2 was found to be 9.8 ms, which was 2 times higher than the pristine TiO2 (4.29 ms).
Keywords: Aromatic amines; DSSC; Electron injection; lifetime; Scattering layer; TiO2

Effect of aromatic rings and substituent on the performance of lithium batteries with rylene imide cathodes - Aher, Jagdish; Graefenstein, Alexander; Deshmukh, Gunvant; Subramani, Kumar; Krueger, Bastian; Haensch, Mareike; Schwenzel, Julian; Krishnamoorthy, Kothandam; Wittstock, Gunther (ChemElectroChem, 2020)
Rylene imides (RIs) are attractive organic battery materials because of the inherent modularity of the molecules. While strong aggregation of RIs is disadvantageous for fast lithium-ion transport in the organic active material, decreasing the solubility of the RIs in battery electrolytes is essential to avoid performance fading. Therefore, the design and synthesis of RIs for lithium batteries is a non-trivial task that must, among other considerations, balance lithium-ion transport in the solid material vs. low solubility by controlling aggregation and packing. We have chosen triphenylamine (TPA) as a substituent which disrupts the aggregation but maintains a low solubility due to increased aromaticity of TPA. We have synthesized three RIs with one, two, and four aromatic units in the core. All of them showed stable specific capacity over 300 charge-discharge cycles. The batteries also showed specific capacities close to their theoretical capacities with 97-99 % coulombic efficiency. The maximum specific energy and specific power were 197 mWh g(-1) and 37 mW g(-1), respectively.
Keywords: lithium-ion batteries; organic cathode material; rylene imides; solubility; triphenylamine

Unsymmetrical squaraine dyes for dye-sensitized solar cells: position of the anchoring group controls the orientation and self-assembly of sensitizers on the TiO2 surface and modulates its flat band potential - Singh, Ambarish Kumar; Maibam, Ashakiran; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Kudlu, Ashwath; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2020)
The position of the anchoring group is systematically changed with a series of alkyl group wrapped donor-acceptor-donor (D-A-D) based squaraine dyes, 4-SQ to 7-SQ, for the use in dye-sensitized solar cells (DSSCs). By this approach, the orientation as well as the self-assembly of the sensitizers can be controlled on the semiconducting TiO2 surface. All of the dyes functionalized with hydrophobic alkyl groups at sp(3)-C and N atoms of the indoline units that is far away from the TiO2 surface to control the self-assembly of dyes and passivate the surface. Controlling both the orientation as well as the self-assembly of the sensitizers synergistically enhances the V-oc of the DSSC device by imparting the dipole moment on the TiO2 surface and minimizing the interfacial charge recombination process of electrons from TiO2 to the oxidized electrolyte, respectively. Further, the presence of a meta-carboxyl group with respect to the N atom of the indoline donor unit for the dyes 4-SQ and 6-SQ makes them nonconductive for the charge injection process, which sheds light on the importance of through-space electron transfer for the device performance. Emission from the relaxed twisted state was found to be a deactivation pathway for 4-SQ on TiO2 and ZrO2, which revealed the importance of structural factors that promote spatial interaction between the sensitizer and metal oxide surface. Computational studies showed the systematic changes in the dipole moment for the sensitizers 4-SQ, 5-SQ, and 6-SQ upon anchoring to the TiO2 surface. The DSSC device performance varied with the position of anchoring groups in the sensitizers. The DSSC device performance of 5-SQ indicates a J(sc) value of 11.35 mA cm(-2), V-oc of 0.698 V, and ff of 77% corresponding to a power conversion efficiency of 6.08% in the presence of 3 equiv of coadsorbent CDCA, which is nearly 1.5 times higher than 6-SQ (V-oc 0.7 V, J(sc) 7.76 mA cm(-2), ff 76%, and eta 4.14%) and 2.6 times higher than 4-SQ (V-oc 0.658 V, J(sc) 4.42 mA cm(-2), ff 78%, and eta 2.28%). IPCE studies revealed the importance of orientation for the charge injection and self-assembly of dyes, as devices with 5-SQ and 6-SQ as a sensitizer showed 94 and 77% response at 578 nm, respectively, which correspond to the aggregated structure of the dye. Mott-Schottky and IPCE experiments showed that the orientation of sensitizers could modulate the V-oc due to the shift in the flat band potential of TiO2.

Concurrent polyvalent interaction and electrocatalysis to improve lithium-sulfur battery performance - Kumar, Subramani; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2022)
Batteries with improved efficiency are desired. Li-S batteries are attractive due to their high specific capacity and energy density. However, sluggish sulfur redox reaction and polysulfide dissolution are significant challenges in Li-S batteries. In this work, we report graphene with doped layer to electrocatalyze the sluggish sulfur redox reaction. The doped layer comprises heteroatoms such as either N or N and S. The doped layer also comprises cations of Ni. We have chosen a ``doped layer on graphene'' over ``doped graphene'' to avoid defects in the basal plane of graphene. We found the doped layer comprising graphene (DLC-G) to electrocatalyze the polysulfide redox reaction. However, the interaction between the doped layer and polysulfide is still weak, hence the dissolution is not suppressed. To circumvent the polysulfide dissolution, graphene with cationic layer was prepared. We found that cations in the layer electrostatically attract the polysulfides due to the polyvalent interaction. Thus, the dissolution is suppressed. While using this material in the Li-S batteries, the specific capacity, energy density and power density were found to be 1345 mAh g(-1), 782 Wh kg(-1) and 4437 W kg(-1), respectively.
Keywords: electrocatalysis; graphene; lithium-sulfur battery; mechanical exfoliation; polyvalent interaction

Instabilities as the origin of large-area self-assembled and aligned organic semiconductor nanocrystals - Venugopalan, Vijay; Jain, Bhanprakash; Mahale, Rajashree Y.; Subramani, Kumar; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2022)
Aligned nanocrystals of organic semiconductors (OSCs) are highly desirable for electronic devices and biomedical and photonic applications. Solution-based wet processing routes have the potential to produce aligned nanocrystals over large areas in small time frames. Herein, we demonstrate that by optimizing the hydrodynamic evaporative processes, controlled long-range crystalline assemblies of OSCs can be achieved (longest nanocrystal similar to 3 mm) purely through physical processes: namely, from fingering instabilities. Self-assembly is achieved here without strong noncovalent interactions such as hydrogen-bonding interactions. Experimentally our approach involves just placing a drop of a solution on an inclined substrate. Nanocrystals with widths of 300-800 nm and lengths of millimeters (length/width aspect ratios >10(5)) are formed in less than 2-8 s. A hydrazine chemiresistive sensor based on the aligned crystalline patterns show unprecedented responsivity (similar to 10(-6)), 2 orders greater than those of stick-slip patterns. Finally, experimental parameters that need optimization to achieve nanocrystal patterns are investigated in detail and pointers to fabricate such OSC nanocrystals are provided.
Keywords: aligned fibers; diketopyrrolopyrrole; fingering instability; nanocrystal arrays; naphthalenediimide; organic semiconductors

Can metal cations electrocatalyze sulfur redox reaction and suppress polysulfide shuttle? - Kumar, Subramani; Swain, Gitanjali; Krishnamoorthy, Kothandam (Batteries & Supercaps, 2023)
In lithium-sulfur (Li-S) batteries, sulfur undergoes various changes. It switches between cyclic structure and linear structure. The charge on the sulfur varies between a neutral state and a negative charge-bearing state. Due to these changes, the sulfur/polysulfide dissolves in the battery electrolyte. Furthermore, the kinetics of the sulfur redox reaction is sluggish. Therefore, a material that can suppress sulfur/polysulfide dissolution and electrocatalyze sulfur redox reaction is needed. We hypothesize that the polysulfide dissolution can be suppressed if the host exhibits polyvalent electrostatic attraction. Polysulfide is a negative charge-bearing molecule; hence the host must comprise multiple positive charges. Nickel cations with other heteroatoms have been explored as a host in Li-S batteries. The heteroatoms impart additional interactions. The easier way to circumvent the effect of heteroatoms is the addition of metal salts. However, metal salts can either exhibit monovalent or divalent attraction with polysulfides. Those interactions are weak and we must have polyvalent interaction. Towards this objective, we have designed and synthesized a material that comprises multiple divalent cations that is also devoid of heteroatoms. The Li-S batteries fabricated using the metal cation immobilized graphene showed a maximum specific capacity of 1022 mAh/g at 0.1 C rate. Among the metal cations, nickel cations showed better performance than cobalt cations. Thus, we demonstrate that metal cations immobilized on Graphene can efficiently electrocatalyze the sluggish sulfur redox reaction and suppress the polysulfide dissolution.
Keywords: electrocatalysis; graphene; lithium-sulfur batteries; metal cations; polysulfides

D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.

Electrocatalytic hydrogen evolution mediated by an organotelluroxane macrocycle stabilized through secondary interactions - Narsimhulu, Gujju; Samuel, Calvin; Palani, Sathishkumar; Dasari, Sai Hemant Kumar; Krishnamoorthy, Kothandam; Baskar, Viswanathan (Dalton Transaction, 2023)
A discrete liphophilic organotelluroxane macrocycle has been found to catalyse the hydrogen evolution reaction (HER) by proton reduction efficiently. The macrocycle is synthesized via chloride abstraction from bis(p-methoxyphenyl) tellurium dichloride (p-MeOC6H5)2TeCl2 (1) by silver salts AgMX4 (MX4 = BF4-, and ClO4-) resulting in in situ generated di-cationic tetraorganoditelluroxane units; two such units are held together by two weak anions mu 2-MX4, bridging to form 12-membered di-cationic macrocycles [((p-MeO-C6H4)2Te)2(mu-O)(mu 2-F2BF2)2]2+ (2) and [((p-MeO-C6H4)2Te)2(mu-O)(mu 2-O2ClO2)2]2+ (3) stabilized via Te-(mu 2-BF4/ClO4), with secondary interactions. The charge is balanced by the presence of two more anions, one above and another below the plane of the macrocycle. Similar reaction at higher temperatures leads to the formation of telluronium salts R3TeX [X = BF4- (4), ClO4- (5)] as a major product. The BF4- anion containing macrocycle and telluronium salt were monitored using 19F NMR. HRMS confirmed the structural stability of all the compounds in the solution state. The organotelluroxane macrocycle 2 has been found to act as an efficient electrocatalyst for proton reduction in an organic medium in the presence of p-toluene sulfonic acid as a protic source. A discrete liphophilic organotelluroxane macrocycle has been found to catalyse hydrogen evolution reaction (HER) by proton reduction efficiently.
Keywords: Anion Transport; Proton-Reduction

Isomer effect on energy storage of π-extended S-shaped double[6]heterohelicene - Kumar, Viksit; Bharathkumar, H. J.; Dongre, Sangram D.; Gonnade, Rajesh; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Angewandte chemie-international edition, 2023)
Recently, chiral and nonplanar cutouts of graphene have been the favorites due to their unique optical, electronic, and redox properties and high solubility compared with their planar counterparts. Despite the remarkable progress in helicenes, pi-extended heterohelicenes have not been widely explored. As an anode in a lithium-ion battery, the racemic mixture of pi-extended double heterohelical nanographene containing thienothiophene core exhibited a high lithium storage capability, attaining a specific capacity of 424 mAh g-1 at 0.1 A g-1 with excellent rate capability and superior long-term cycling performance over 6000 cycles with negligible fade. As a first report, the pi-extended helicene isomer (PP and MM), with the more interlayer distance that helps faster diffusion of ions, has exhibited a high capacity of 300 mAh g-1 at 2 A g-1 with long-term cycling performance over 1500 cycles compared to the less performing MP and PM isomer and racemic mixture (150 mAh g-1 at 2 A g-1). As supported by single-crystal X-ray analysis, a unique molecular design of nanographenes with a fixed (helical) molecular geometry, avoiding restacking of the layers, renders better performance as an anode in lithium-ion batteries. Interestingly, the recycled nanographene anode material displayed comparable performance. A pi-extended double heterohelical nanographene of thienothiophene core fused with two hexabenzocoronene units exhibits excellent performance as an anode in a lithium-ion battery. The isomer (PP and MM) with more interlayer distance exhibited a high lithium storage capability compared to the other isomer and racemic mixture. Helical nanographene anodes display excellent rate capability, superior long-term cycling performance, and recyclability.image
Keywords: Battery; graphene; Li-ion battery; nanographene; Organic Electrode Material

Linear polymer comprising dual functionalities with hierarchical pores for lithium ion batteries - Aher, Jagadish D.; Palani, Sathishkumar; Krishnamoorthy, Kothandam (Chemelectrochem, 2023)
Organic materials with carbonyl, azo, nitrile and imine moieties are widely used in lithium batteries. The solubility of these materials in battery electrolytes is an issue. Aggregation of the organic molecules can suppress the solubility, but the accessibility of lithium-ion is hindered. Therefore, insoluble porous organic materials are desired. Herein, we synthesized a linear polymer with carbonyl and azo functionalities. Due to the presence of easily isomerizable azo moiety, a porous polymer was obtained. The polymer showed nano and micropores. The battery with the porous polymer showed an impressive specific capacity of 400 mA h/g at 0.2 A/g. If the battery is pre-conditioned, the specific capacity increased to 615 mA h/g at the same current density. The post-mortem analysis of the battery confirmed that the polymer didn't dissolve in the battery electrolyte. The control material is a small molecule with carbonyl and azo moieties that showed a poor specific capacity of 40 mA h/g indicating the necessity to have a hierarchically porous dual-functional polymer. Polymers for batteries: A linear polymer with micro and Nano pores with azo and carbonyl functionalities renders increased accessibility to Li ions after preconditioning. During charge-discharge experiment Azo-Carb-PDI electrode had impressive discharge capacity of 469 mA h/g after 500 cycle which is almost 15 times higher than the monomer (Azo-PDI-Azo, 30 mA h/g after 100 cycle).image
Keywords: azo polymer; carbonyl; Li-ion battery; porous polymer; Rylene-imide

Modular TiO2-squaraine dyes/electrolyte interface for dye-sensitized solar cells with cobalt electrolyte - Singh, Ambarish Kumar; Sudhakar, Vediappan; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2023)
Strategies to diminish both charge recombination and aggregation of dyes on the photoanode by functionalizing the sensitizer with alkyl groups is the best approach to achieve high dyesensitized solar cell (DSSC) efficiency. Development of such a photoanode with NIR-active dyes which is compatible with a cobalt electrolyte is important to enhance the photovoltaic performance. In this report, alkyl-group-wrapped donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been used for DSSC device characterization with a cobalt electrolyte. Surface passivation of photoanode was varied systematically by the extent of functionalization with alkyl groups to avoid charge recombination. DSSC device performance of 5.92% was achieved for an alkyl-group-wrapped squaraine dye with a cobalt electrolyte. Hence, appending the alkyl groups on the donor unit of squaraine dyes helps passivating the photoanode, whereas introducing hydrophilic groups provides a leaky surface where oxidized electrolyte species reach the titanium-metal-oxide surface which promotes the charge recombination process.
Keywords: counter-electrode; DSSC device efficiency; Dye-sensitized solar cells; Electrolytes; unsymmetrical squaraine dye

Organic field effect transistors comprising copolymers synthesized without structure-directing moieties with enhanced carrier mobility - Swain, Gitanjali; Javaregowda, Bharathkumar H.; Dambhare, Neha V.; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2023)
Conjugated materials are synthesized by C-C bond formation reactions. Trimethyltin and boronic acid are two widely used structure-directing moieties. While using the ethynyl moiety as a part of the monomer, additional structure-directing moieties are not needed. However, ethynylene will be part of the conjugated material. Often, the polymers with an ethynylene moiety negatively impact the polymers' properties. However, the ethynylene moiety could minimize the dihedral angle if the monomer has steric functionalities. For example, BODIPY is an attractive monomer due to its high molar extinction coefficient, partial quinoidal character, and high quantum yield. However, materials based on BODIPY exhibited poor charge carrier mobility due to steric hindrance generated by four methyl groups. Herein, we copolymerize BODIPY with ethynylene comprising i-indigo and thieno-i-indigo. The copolymer with thieno-i-indigo showed increased molecular weight and significantly reduced band gap compared to the copolymer with i-indigo. The copolymer with i-indigo showed immeasurably low hole transport mobility. On the other hand, the copolymer with thieno-i-indigo exhibited 0.003 cm2V(-1) s(-1). These measurements were made using field effect transistors. We also measured the charge carrier mobility using the space charge-limited current method. Both copolymers exhibited a mobility of 10(-3) cm(2) V-1 s(-1).
Keywords: acetylene linkage; BODIPY; field effect transistor; iso-indigo; Sonogashira coupling; thienoisoindigo

Steric and electronic effect in unsymmetrical squaraine dyes for dye-sensitized solar cells - Nawghare, Indrajeet S.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of physical chemistry C, 2023)
Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO2/electrolyte interface and the photovoltaic device performance in dye-sensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overpotential associated with the dye-regeneration process and make the dye-TiO2 interface compatible with various electrolytes. Furthermore, an in-built steric feature by means of introducing linear/branched alkyl groups in the sensitizer is important in controlling the aggregation of dyes on the TiO2 surface. Hence, to integrate both steric and electronic properties, a series of alkyl group-wrapped unsymmetrical squaraine dyes (SQ-X) with electron-donating and -withdrawing groups have been designed, synthesized, and utilized for DSSC device fabrication. These dyes are functionalized with alkyl groups at both sp(3)-C and N-atoms of the indoline donor moiety at the nonanchoring side to have a similar steric feature. Photophysical and electrochemical studies revealed that the HOMO and LUMO energy levels of the SQ-X series of dyes have been modulated systematically with sufficient driving forces for both charge injection and dye-regeneration processes with iodolyte (I-/I-3(-)) electrolyte. In the presence of electron-donating groups in SQ-X (where X = -NPh2 and -OMe), the HOMO energy levels are less positive than SQ-H, whereas the presence of electron-withdrawing groups such as -CO2Me, -CN, and -NO2 pushed the HOMO energy levels toward more positive potentials. Enhanced photovoltaic performances have been obtained for the dyes containing electron-donating groups, where the dye with the -NPh2 group showed a maximum of eta 7.03% (V-OC 708 mV, J(SC) 13.16 mA cm(-2), and ff 78%). The dye with the strong electron-withdrawing group -NO2 showed an efficiency of 1.49% (V-OC = 634 mV, J(SC) = 3.13 mA cm(-2), and ff 75%). As the dyes with the electron-withdrawing group possess deep positive HOMO energy levels, the DSSC device characterization has been investigated with the Cu+/2+ redox shuttle. The reduced device performance of electron-withdrawing-group-containing dyes is due to the unfavored charge distribution in the LUMO compared to the presence of electron-donating-group-containing dyes, and it was supported by the difference in the charge injection efficiency.
Keywords: cobalt; Donor; Dynamics; Organic dyes

Visible-light-active unsymmetrical squaraine dyes with 1 V of open-circuit voltage for dye-sensitized solar cells - Singh, Amrita; Kumar Singh, Ambarish; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ChemPhotoChem, 2023)
A series of alkyl-group-functionalized, aniline- and indoline-donor-based, unsymmetrical visible-light-active squaraine dyes, AM1-3, were designed and synthesized. Dye-sensitized solar cell (DSSC) devices were fabricated with both I-/I-3(-) and [Cu(tmby)(2)](+/2+) electrolytes. DSSC devices sensitized with the AM1 and AM2 dyes showed relatively high-power conversion efficiency of 7.44 % and 7.22 %, respectively with I-/I-3(-) in the absence of chenodeoxycholic acid (CDCA) than those of the AM3 dye (5.41 %). The [Cu(tmby)(2)](+/2+) electrolyte along with poly(3,4-ethylenedioxythiophene) (PEDOT) as cathode material showed excellent open-circuit potentials (V-OC) of 1030, 1025, and 1001 mV with the DSSC efficiency of 8.05 %, 7.96 %, and 5.84 %, respectively, for the AM1, AM2, and AM3 dyes in the absence of CDCA. Here, the AM1 dye exhibited the maximum DSSC efficiency of 8.05 % and V-OC of 1030 mV, which is the highest obtained efficiency and V-OC for the visible-light active zwitterionic unsymmetrical-squaraine dye with copper-based electrolyte.
Keywords: Cu electrolytes; dihedral angle; Dye-sensitized solar cells; open circuit voltage; squaraine dyes

Visible-light-active unsymmetrical squaraine dyes with pyridyl anchoring groups for dye-sensitized solar cells - Deshmukh, Shivdeep Suresh; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Langmuir, 2023)
Visible-light-active alkyl group-wrapped unsymmetrical squaraine dyes SD1-SD3 were synthesized, featuring an indoline donor and pyridine and carboxylic acid anchoring groups. Their photophysical, electrochemical, and photovoltaic characteristics were examined by fabricating a dye-sensitized solar cell (DSSC) device. Both carboxylic acid and pyridine anchoring groups containing squaraine dyes SD3 and SD2 possess similar photophysical and electrochemical characteristics. However, their photovoltaic performances were completely different. The SD3 dye with the carboxylic acid anchoring group displayed a DSSC device efficiency of 7.20% (V-OC 0.81 V; J(SC) 12.29 mA/cm(2)) using iodolyte (I-/I-3(-)) electrolyte, compared to SD1 (V-OC 0.659 V; J(SC) 4.97 mA/cm(2); and eta - 2.34%) and SD2 (V-OC 0.629 V; J(SC) 1.68 mA/cm(2); and eta - 0.84%), which were featured with pyridyl anchoring groups. These results were attributed to dye loading on the Lewis and Br & oslash;nsted acidic sites of TiO2 and the importance of aggregated structures for photocurrent generation. In the incident photon-to-current efficiency (IPCE) analysis, SD1 dye-sensitized devices exhibited photocurrent generation from both monomeric and aggregated dyes on the TiO2 surface. In contrast, SD2 showed photocurrent generation solely from aggregated states. Despite the introduction of long alkyl chains to reduce dye aggregation and charge recombination, the results indicated preferential charge injection from only the aggregated SD2 dye on TiO2. Fluorescence-quenching experiments indicated an efficient charge transfer from the aggregated SD2 dye to TiO2 compared to that of the monomeric dye. Cosensitization, a method to enhance the light-harvesting efficiency and photocurrent generation in DSSCs, was explored by simultaneously cosensitizing pyridyl-based dyes (SD1 and SD2) with a blue-colored carboxylic acid-based squaraine dye SD4. IPCE analysis demonstrated that both SD1 and SD4 contributed to generating a photocurrent of 9.11 mA/cm(2). The sequential cosensitization of SD1 and SD4 with the coadsorbent CDCA showed the highest performance, with a V-OC of 0.663 V, a J(SC) of 11.43 mA/cm(2), and an efficiency (eta) of 5.20%.
Keywords: co-sensitization; Design; Emmision; Fluorescent Dyes; High-Efficiency; Organic Dye; Ring

Aniline and indoline donors based far-red active unsymmetrical squaraine dyes for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2024)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on the metal-oxide surface by appending the alkyl groups around the donor or pi-spacer unit of the dye is a potential approach to enhance DSSC efficiency. Further, rigidification of the dye structures by cyclization modulates the photophysical properties of the sensitizer. Here a series of donor-acceptor-donor (D-A-D) type far-red active unsymmetrical squaraine dyes (SQA) have been designed and synthesized, where N,N-dimethylaniline, methylated- and branched-indoline have been used as donor units. These dyes showed absorption between 629-654 nm (lambda max) with the molar extinction coefficient of 1.49-1.94x105 M-1 cm-1. Systematic enhancements in DSSC device efficiency have been observed due to the cyclization and alkyl-groups incorporation in this set of dyes which were further enhanced with the addition of chenodeoxycholic acid (CDCA). The highest DSSC device efficiency of 4.78 % (Jsc of 8.77 mA/cm2 and Voc of 692 mV) has been achieved for SQA3. The IPCE profile of SQA dyes indicates the contribution of aggregated structures for the photocurrent generation. Further, co-sensitization of SQA3 dye with a complementary visible light active dye AK4 showed the enhanced device efficiency of 6.27 % with panchromatic IPCE response. Dye rigidification, and controlled aggregation of dyes on TiO2 by means of cyclization of donor unit and introducing the alkyl groups in the dye structure synergistically improve the dye-sensitized solar cell (DSSC) device performance. Donor-Acceptor-Donor (D-A-D) based unsymmetrical squaraine dye SQA3 showed the DSSC device performance of 4.78 %.image
Keywords: co-sensitization; dye-sensitized solar cell; effect of alkyl chain; molecular planarity; squaraine dye

Effect of position of donor units and alkyl groups on dye-sensitized solar cell device performance: indoline-aniline donor-based visible light active unsymmetrical squaraine dyes - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Om., 2024)
Indoline (In) and aniline (An) donor-based visible light active unsymmetrical squaraine (SQ) dyes were synthesized for dye-sensitized solar cells (DSSCs), where the position of An and In units was changed with respect to the anchoring group (carboxylic acid) to have In-SQ-An-CO2H and An-SQ-In-CO2H sensitizers, AS1-AS5. Linear or branched alkyl groups were functionalized with the N atom of either In or An units to control the aggregation of the dyes on TiO2. AS1-AS5 exhibit an isomeric pi-framework where the squaric acid unit is placed in the middle, where AS2 and AS5 dyes possess the anchoring group connected with the An donor, and AS1, AS3, and AS4 dyes having the anchoring group connected with the In donor. Hence, the conjugation between the middle squaric acid acceptor unit and the anchoring -CO2H group is short for AS2, AS5, and AK2 and longer for AS1, AS3, and AS4 dyes. AS dyes showed absorption between 501 and 535 nm with extinction coefficients of 1.46-1.61 x 10(5) M-1 cm(-1). Further, the isomeric pi-framework of An-SQ-In-CO2H and In-SQ-An-CO2H exhibited by means of changing the position of In and An units a bathochromic shift in the absorption properties of AS2 and AS5 compared to the AS1, AS3, and AS4 dyes. The DSSC device fabricated with the dyes contains short acceptor-anchoring group distance (AS2 and AS5) showed high photovoltaic performances compared to the dyes having longer distance (AS1, AS3, and AS4) with the iodolyte (I-/I-3(-)) electrolyte. DSSC device efficiencies of 5.49, 6.34, 6.16, and 5.57% have been achieved for AS1, AS2, AS3, and AS4 dyes, respectively; without chenodeoxycholic acid (CDCA), small changes have been observed in the device performance of the AS dyes with CDCA. Significant changes have been noted in the DSSC parameters (open-circuit voltage V-OC, short-circuit current J(SC), fill factor ff, and efficiency eta) for the AS5 dye while sensitized with CDCA and showed highest DSSC efficiency of 8.01% in the AS dye series. This study revealed the potential of shorter SQ acceptor-anchoring group distance over the longer one and the importance of alkyl groups on the overall DSSC device performance for the unsymmetrical squaraine dyes.

Far-red active unsymmetrical squaraine dyes containing N-arylated indoline donors for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Jayaraj, Nithyanandhan (Photochemistry and Photobiology, 2024)
Squaraine dyes possess sharp far-red active transition with high extinction coefficient and form aggregates on TiO2 surface. Aggregation of dyes on TiO2 has been considered as a detrimental factor for DSSC device performance, which can be controlled by appending alkyl groups to the dye structures. Hence by integrating alkylated (alkyl groups with both in-plane and out-of-plane) aryl group with indoline moiety to make it compatible with other electrolytes and for controlling the dye-aggregation, a series of squaraine acceptor-based dyes SQA4-6 have been designed and synthesized. SQA4-6 dyes showed absorption between 642 and 653 nm (lambda max), photophysical and electrochemical studies indicated that the HOMO energy levels of this sets of dyes are well aligned with the potentials of I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$ and [Co(bpy)3]2+/3+ redox shuttles for better dye regeneration process. DSSC device efficiency of 3% has been achieved for SQA5 dye with iodolyte (I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$) electrolyte in the presence of 0.3 mM of chenodeoxycholic acid (CDCA). The IPCE profile of DSSC device fabricated with SQA4-6 dyes indicated the contribution of aggregated structures for the photocurrent generation. Dye-sensitized solar cell (DSSC) device efficiency of 3% (Jsc 5.72 mA cm-2, Voc 662 mV and ff 79%) has been achieved for an unsymmetrical squaraine dye, SQA5 with iodolyte electrolyte and the incident photon to current efficiency (IPCE) profile indicates the contribution of aggregated structures for the photocurrent generation.*image
Keywords: aggregation of dye; arylation on N-atom of indoline donor; dye-sensitized solar cell; squaraine dye

MOFite: a high-density lithiophilic and scalable metal-organic framework anode for rechargeable lithium-ion battery - Gaber, Safa; Mohammed, Abdul Khayum; Javaregowda, Bharathkumar H.; Martinez, Jose Ignacio; Sanchez, Pilar Pena; Gandara, Felipe; Krishnamoorthy, Kothandam; Shetty, Dinesh (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: conjugated MOF; Energy storage; lithium ion battery; Metal-organic framework; scalable synthesis

Polyvalent interaction and confinement to suppress polysulfide dissolution and improve electrocatalysis - Bharathkumar, H. J.; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Chen, Dehong; Caruso, Rachel A.; Krishnamoorthy, Kothandam (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: cathode material; HIGH-CAPACITY; Particles; SULFUR CATHODE

Shuttle balance between lithiophilic functionalities substituted on conjugated polymers to improve lithium-ion diffusion and cycling stability of batteries - Kargude, Radhakisan; Javaregowda, Bharathkumar H.; Palani, Sathishkumar; Singh, Anup K.; Krishnamoorthy, Kothandam (Macromolecules, 2024)
Herein, we report the design and synthesis of i-Indigo and trans-1,2-di(2-thienyl)ethylene (TVT) comprising copolymers with various side chains that are used as anode-cum-binder in Li-ion batteries. The TVT disrupts the crystallinity, and the i-Indigo renders the handle for unsymmetrical substitution. Polymer P1 comprises alkyl chains on i-Indigo, whereas P2 comprises an alkyl chain and a chain with a urethane moiety as another side chain. Polymer P3 comprises i-Indigo with a urethane moiety and triethylene glycol as side chains. The i-Indigo in P4 is substituted with triethylene glycol and alkyl chains as side chains. These polymers were found to be amorphous with pi-pi stacking due to the extremely small torsional angle imparted by TVT moieties. All of these polymers showed comparable specific capacity while used as an anode in Li-ion batteries due to the presence of a common conjugated backbone. However, the battery metrics varied significantly while the current density of the batteries varied between 0.1 and 2.0 A g(-1). P1 and P2 showed a very close recovery of specific capacity at 0.1 A g(-1) before and after various current densities. However, polymers P3 and P4 did not recover from the specific capacity fading due to the presence of triethylene glycol side chain that degraded. Polymer P2 with an alkyl side chain and a chain with a urethane moiety showed stable performance over 2000 charge-discharge cycles. Contrary to this, the stability of polymers with triethylene glycol side chains decreased over 2000 charge-discharge cycles. Polymer P2 with a urethane side chain also showed improved Li-ion diffusion because the urethane moiety facilitated better Li-ion transport.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole

Triazatruxene amine donor-based visible-light-responsive unsymmetrical squaraine dyes for dye-sensitized solar cells - Ingole, Kiran Balaso; Deshmukh, Shivdeep Suresh; Verma, Tushar Singh; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Optimized charge-transfer dynamics at the dye-TiO2/electrolyte interface are required for an enhanced dye-sensitized solar cell (DSSC) device performance. Such an optimized interface enhances the charge-injection, dye-regeneration, and diminished charge-recombination processes, synergistically enhancing the device efficiency. In this study, octupolar-structured sensitizers are designed to improve the interaction between the dye and the redox electrolyte for increasing the dye-regeneration process upon photoexcitation. Accordingly, a set of unsymmetrical squaraine dyes with indoline and triazatruxene amine donor-based D-A-D dyes are designed (KV1-KV3), synthesized, and sensitized with a semiconducting metal oxide (TiO2) film. The sensitizer forms a monolayer on the TiO2 surface, leading to a dye-dye interaction, which broadens the absorption spectrum. The N atom of the triazatruxene amine donor was left unsubstituted in KV1, whereas a hexyl chain was installed in KV2 and KV3 and a branched alkyl chain was installed on the core N atoms in KV3 to control the self-assembly of dyes on the TiO2 surface. Self-assembly of alkyl groups wrapped in KV1-KV3 dyes on the TiO2 surface aids surface passivation and broadens the absorption profile, improving the light-harvesting capabilities. The DSSC devices based on KV2 exhibited a high power conversion efficiency of 7.85% (V-oc = 794 mV, J(sc) = 14.76 mA/cm(2), and FF = 67%), with an onset incident photon-to-current conversion efficiency response from 680 nm.
Keywords: aggregationof dyes; Dye-sensitized solar cells; metal-free organic dyes; self-assembly of dye; squaraine dyes; triazatruxene

Visible, far-red, and near-infrared active unsymmetrical squaraine dyes based on extended conjugation within the polymethine framework for dye-sensitized solar cells - Singh, Amrita; Singh, Ambarish Kumar; Dixit, Ruchi; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Alkyl group wrapped visible, far-red, and NIR active unsymmetrical squaraine dyes with pi-extension in the polymethine framework-based AM4-AM7 have been designed, synthesized, and utilized as sensitizers for dye-sensitized solar cells. To extend the pi-conjugation within the polymethine framework, thiophene moieties have been incorporated between the donor and acceptor moieties. Absorption spectroscopic studies revealed that pi-extension with each -C & boxH;C- unit resulted similar to 100 nm of redshift in the charge transfer transition with the lambda(maximum) of 541, 643, 747, and 833 nm for AM4, AM5, AM6, and AM7 dyes, respectively, with the molar extinction coefficient of >10(5) M(-1)cm(-1). The pi-extended conjugation-based AM6 and AM7 dyes showed improved light-harvesting efficiency (LHE), where the AM7 dye showed an LHE of 386 nm at 60%. Electrochemical studies of AM dyes revealed that the HOMO energy level of the sensitizers has been modulated systematically. Further, pi-extension within the polymethine framework showed a dramatic effect on V-OC, J(SC), and device efficiency when move from visible active AM4 to far-red active to NIR active AM7 dyes. The DSSC efficiencies of 7.35, 5.18, 0.08, and 0.053% have been achieved with the I-/I-3(-) electrolyte (Z-50) for the AM4, AM5, AM6, and AM7 dyes, respectively. Further, AM4 dye has been cosensitized with AM5, AM6, and AM7 dyes, where AM4:AM5 (1:1) composition achieved the maximum efficiency of 8.12% with I-/I-3(-) electrolyte (Z-50) compared to the other cosensitization compositions.
Keywords: aggregation of dyes; DSSC device efficiency; light-harvesting efficiency; pi-extension; polymethine framework; squaraine dyes

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene

Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

Effect of cyclization and alkyl group wrapping in visible-light-active unsymmetrical squaraine dyes for dye-sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Shivankar, Bhavana R.; Siby, Jesna; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
A series of alkyl group-appended indoline- and carboxylic acid-functionalized indolenine-based visible-light-active unsymmetrical squaraine dyes, SQA7-10, were designed, synthesized, and utilized for the dye-sensitized solar cells device fabrication. The number of alkyl group has been increased systematically on the indoline moiety to control the self-assembly of dyes on TiO2 and to passivate the photoanode that helps in improving the open-circuit voltage (V-OC) by avoiding the charge recombination process. SQA7-10 dyes showed an absorption between lambda(max) 536-540 nm, with molar extinction coefficients of 1.62-2.13 x 10(5) M-1 cm(-1) in CH3CN. Further, ultraviolet-visible (UV-vis) studies on TiO2 indicated the formation of H-aggregated dyes (505-510 nm), which can be controlled by appending the alkyl groups. The energy levels of the highest occupied molecular orbital (HOMO) of these dyes are well aligned with the Nernst potentials of I-/I(3)(-)electrolyte and [Cu(tmby)(2)](+/2+) electrolytes with sufficient overpotentials required for the dye regeneration process. DSSC devices made with these dyes showed systematic enhancements of open-circuit voltage (V-OC) and device efficiency with respect to alkyl group incorporation for SQA7-10 with I-/I-3(-) electrolytes. All of the SQA dyes exhibited the device V-OC of more than 805 mV, where the introduction of alkyl groups systematically enhanced the V-OC in the order of SQA7 (805 mV) < SQA8 (829 mV) < SQA9 (843 mV) < SQA10 (862 mV) without any addition of CDCA. Within the SQA dye series, SQA10 dye has achieved the highest DSSC device efficiency of 7.52% (J(sc) of 11.16 mA/cm(2), V-oc of 862 mV, and ff of 78%) with I-/I-3(-) electrolyte, whereas use of [Cu(tmby)(2)](+/2+) redox shuttle with SQA10 showed enhanced V-oc (1080 mV) and device efficiency (8.35%). The IPCE profile for the device fabricated with SQA dyes showed good response at 480 and 560 nm, which indicates the photocurrent generation from the aggregated structures.
Keywords: aggregation of dyes; charge recombination; Dye-sensitized solar cells; indoline and indolenine donors; visible-light-activeunsymmetrical squaraine dye

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle

Long cycling stability imparted to li-ion batteries by conjugated polymers with low dihedral angles and high electron density on functional groups - Kargude, Radhakisan; Srinivasalu, Hari Haran; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam (ACS Applied Polymer Materials, 2025)
In conjugated polymers, dihedral angles at bonds connecting their monomers impact the polymers' properties such as the packing of the polymer chains, bandgap, and conductivity. These properties are expected to impact the performance of rechargeable Li-ion batteries because the Li-ion transport and conductivity of the polymers are two important parameters. To understand this, we designed and synthesized two polymers with two different dihedral angles. The polymer, Poly(EDOT-DPP), comprising diketopyrrolopyrrole (DPP) and ethylenedioxythiophene (EDOT) as monomers, showed a low dihedral angle of 2 degrees. On the other hand, the polymer, Poly(EDOT-i-Ind), comprising EDOT and i-Indigo (i-Ind) showed a dihedral angle of 17 degrees. Density functional theory (DFT) studies showed that the electron density at the carbonyl moiety of EDOT-DPP is higher than that of EDOT-i-Ind. This resulted in a higher Li+ binding energy of -3.665 eV for EDOT-DPP and a lower Li+ binding energy of -3.464 eV for EDOT-i-Ind. Battery electrodes were fabricated using either Poly(EDOT-DPP) or Poly(EDOT-i-Ind) with multiwalled carbon nanotubes as conducting fillers in the absence of any binders. The Li+ ion diffusion coefficient ( D Li + ) measured for the as prepared batteries based on Poly(EDOT-DPP) was found to be 3.9 x 10-19 cm2/s, which is slightly higher than that found for Poly(EDOT-i-Ind). However, after 2000 cycles, the D Li + increased by about two orders of magnitude for both polymers. Due to the low dihedral angle in the case of Poly(EDOT-DPP), the D Li + was found to be 21% higher than that of Poly(EDOT-i-Ind). The higher binding of Li+ ions with Poly(EDOT-DPP) and Li+ ion diffusion improved the specific capacity and cycling performance of batteries fabricated with this polymer. At a current density of 0.2 A/g, Poly(EDOT-DPP) showed a 39% higher specific capacity than the Poly(EDOT-i-Ind) polymer after 2000 cycles. The batteries also showed stable performance over 2000 cycles with an insignificant decrease in specific capacity.
Keywords: dihedral angle; diketopyrrolopyrrole; i-indigo; Li-ion battery; Li-ion transport

Mechanochemical large-scale rapid synthesis of ultrapure sodium hexafluorophosphate - Senthilkumaran, Marimuthu; Javaregowda, Bharathkumar H.; Rajendran, Prakash Babu; Balasubramanian, Rajalakshmi; Ajithkumar, Thalasseril G.; Ravindranathan, Sapna; Krishnamoorthy, Kothandam (ChemPlusChem, 2025)
Among the sodium battery electrolytes, sodium hexafluorophosphate (NaPF6) exhibits superior conductivity, anodic stability, and stable cathode electrolyte interface compared to other electrolytes. Therefore, the synthesis of pure NaPF6 through a simple process is very important. Usually, NaPF6 is synthesized using HF. In our approach, NaPF6 is synthesized by grinding dry ammonium hexafluorophosphate (NH4PF6) and sodium metal. Sodium injects an electron into the ammonium ion, which results in the formation of ammonia and hydrogen. The gram scale synthesis is completed in about 30 min. Purification of the product is not needed. The product purity is confirmed by various spectroscopic and electrochemical techniques. Usually, NaPF6 comprises NaF, HF, and solvents as impurities that affect the performance of SIBs. It has been confirmed that the NaPF6 synthesized by our mechanochemical approach in the absence of solvent is devoid of impurities despite the absence of product purification step. Furthermore, the synthesis of pure NaPF6 (250 g) is demonstrated using a grinder used as household item in cooking Indian pancakes, which costs about 300 USD. The duration of the synthesis of 250 g pure NaPF6 is 1 h. The purity of this sample is comparable to that of NaPF6 (5 g) synthesized using mortar and pestle.
Keywords: ammonium hexafluorophosphate; Batteries; carbonates; sodium hexafluorophosphate; sodium vanadium phosphate

Modulation of lithium ion transport and cycling stability using rigid and flexible urethane moieties on the backbone of polymers - Kargude, Radhakisan; Rajendran, Prakash Babu; Kika, Sharmin Percy; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2025)
Graphite is the anode of choice for lithium-ion batteries. Due to volume change and poor conductivity of inorganic materials, they do not show comparable performance to that of graphite. Conjugated polymers are attractive because of their modularity and ease of synthesis. Herein, we report three polymers based on diketopyrrolopyrrole (DPP) as the anode. In an energy device, stored charges are due to a diffusive and capacitive component. Increasing the capacitive component is a challenge in both organic and inorganic systems. In our polymers, we installed urethane moieties that increase the capacitive component. The excellent Li+ ion transporting urethane moiety is part of the polymer chain. The Li+ ion transport is also impacted by the packing of the polymer chain. Therefore, the DPP units and urethane moieties are connected with either an alkyl chain, phenyl or biphenyl. The polymers with either alkyl or phenyl spacers showed stable cycling stability over 4000 charge-discharge cycles. On the other hand, the specific capacity of the batteries comprising a polymer with biphenyl started decreasing after 500 charge-discharge cycles. This is due to the solubility of the polymer in the battery electrolyte. The polymer with a phenyl spacer showed a higher Li+ ion diffusion coefficient due to the space generated between the polymer chains. The X-ray photoelectron spectroscopy analysis showed that the Li+ ions are bound to carbonyls, indicating the role of urethane in the charge transport. The polymer with an alkyl spacer showed a very high specific capacity of 600 mAh/g (1500th cycle) at a current density of 0.2 A/g, which is much higher than the theoretical capacity of graphite (372 mAh/g). The charge storage in all these polymers is dominated by a capacitive component, with the highest metric of 81% shown by a polymer with an alkyl spacer.
Keywords: Cycling stability; diketopyrrolopyrrole; high capacity; lithium-ion battery; non-conjugatedpolymer; urethane

Visible-light active π-extended unsymmetrical squaraine dyes for dye-sensitized solar cells: steric effects for controlling the aggregation of dyes - Jadhav, Avinash P.; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2025)
The dye-anchored TiO2 photoanode plays a vital role in the light harvesting and charge separation processes in dye-sensitized solar cells. Aggregation of dyes (H- and J-type) on the TiO2 surface is a facile process due to the presence of a periodical dye anchoring sites on the exposed facet of titania, and such self-assembled dye structures help broadening the absorption profile. However, photocurrent generation from such aggregated structure is a challenging task in dye-sensitized solar cell devices. Hence, controlling the dye aggregation on the TiO2 surface is an important aspect. Controlling the aggregation of dyes by which (i) an enhanced photocurrent generation (J SC) and (ii) enhanced V OC can be achieved by including the steric factors to the dye design principles, the steric factor in the sensitizer may help passivate the TiO2 surface to avoid the charge recombination process between electrons present in TiO2 and the oxidized electrolyte. On the other hand, extension of pi-conjugation in a sensitizer helps enhance the light absorption in the visible region besides modulating the HOMO and LUMO energy levels. Hence, synergizing both pi-extensions along with features that control the dye aggregation has been considered in designing visible active squaraine dyes. A thiophene pi-spacer was inserted in between a visible-light active unsymmetrical squaraine unit and a cyanoacetic acid acceptor unit to provide the AJ1 and AJ2 dyes. Though both the dye molecules possess a similar pi-framework, the AJ2 dye was functionalized with both in-plane and out-of-plane alkyl groups to decrease the aggregation of dyes on the TiO2 surface compared to AJ1. The AJ1 and AJ2 dyes absorbed at 560 nm with shoulder peaks appeared at 528 nm, which can be assigned to vibronic progression (1082 cm-1), and additional characteristic peaks of thiophene appeared at 392 nm with the molar extinction coefficient of 1.16-1.19 x 105 M-1 cm-1 in CH3CN. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of iodolyte (I-/I3 -) electrolyte with sufficient overpotentials for charge injection and dye regeneration processes, respectively. The highest DSSC device efficiency of 7.37% (J SC 14.44 mA/cm2, V OC 0.771 V, ff 67.1%) was achieved for the AJ2 dye with iodolyte (I-/I3 -) electrolyte in the presence of 2 equiv of optically transparent coadsorbent chenodeoxycholic acid (CDCA), which showed a good IPCE response in between 400 and 700 nm. Further, cosensitization of visible-light active AJ1, AJ2, and SQA10 dyes with a complementary far-red active SQS4 dyes showed the device efficiencies of 5.53% (AJ1:SQS4:CDCA), 7.14% (AJ2:SQS4:CDCA), and 7.18% (SQA10:SQS4:CDCA) with a good IPCE response in the 400-720 nm region.
Keywords: cosensitization; Dye aggregation; Dye-sensitized solar cells; pi-extended squaraine dye; visible-lightactivedyes

Architecting nanographenes for efficient energy storage by tailoring molecular conformation and packing - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Santhosh Babu, Sukumaran (Journal of Materials Chemistry A, 2026)
Structural tuning of electrode materials to enhance electron transport, ion storage capacity, and Li+ diffusion is crucial for developing high-performance lithium-ion batteries (LIBs). In this context, organic functional materials are attractive candidates. Herein, we report a unique molecular design of regioisomeric nanographenes (NGs) with distinct geometries, packing, and topologies for lithium storage as LIB anodes. The nonplanar architectures suppress layer restacking compared to planar analogues, leading to improved electrochemical performance. The pi-extended helical NG 36NG, with larger interlayer spacing and a unique helical geometry, enables faster Li+ diffusion and delivers a higher specific capacity of 719.93 and 203.01 mAh g-1 at 0.1 and 1 A g-1, respectively, with stable performance over 6000 cycles, outperforming 27NG (525.46 and 113.17 mAh g-1 at 0.1 and 1 A g-1, respectively). Single-crystal X-ray analysis reveals markedly different molecular arrangements, directly correlating topology and packing with Li+ storage. This work highlights the critical role of molecular topology in LIB anodes and motivates the design of tailored pi-extended helical nanographenes for energy-storage applications.

Auxiliary triazatruxene donor-based squaraine dyes for dye-sensitized solar cells: cis- and trans- configuration of dyes for modulating photophysical and electronic properties - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemistry-an Asian Journal, 2026)
In DSSCs, dye regeneration efficiency and dye aggregation on the TiO2 surface can be modulated by using bulky aromatic donors wrapped with alkyl groups. Introduction of rigid aromatic rings around the donor unit of a dye will directly impact the driving force for electron injection and dye regeneration of a dye. In this work, we designed and synthesized KNS dyes with an auxiliary TAT donor integrated with a visible active squaraine dye. Here, octupolar-structured auxiliary TAT wrapped with alkyl groups is used as a strong donor and shelter to reduce the dye aggregation and charge recombination process. Further, to improve the light-harvesting efficiency and incident photon-to-current conversion efficiency of DSSC devices fabricated with KNS dyes, the central squaric acid unit has been modified by appending the electron-withdrawing dicyano group at the central squaric unit, and the trans-configured KNS1 dye was converted to cis-configured KNS2 dye. The power conversion efficiency of devices based on the KNS dyes was studied with and without 3 equivalents of CDCA by using the I-/I3 - electrolyte. Out of these devices, the KNS1: CDCA (1:3) based cell exhibited the best PCE of 6.25% with V OC of 793 mV, J SC of 11.08 mA cm-2, and ff of 71%.
Keywords: Bulky donor unit; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

Metal films from a single source and their application in nanoporous filtration synthesis, electromagnetic interference shielding, and electroadhesion - Veerasubash, Muthupandi; Birajdar, Sarika Hanamant; Kika, Sharmin Percy; Senthilkumaran, Marimuthu; Deshpande, Karan; Shevate, Rahul; Krishnamoorthy, Kothandam (ACS Omega, 2026)
Electroless metal depositions are carried out by a series of reduction steps involving multiple metal ions to obtain a film on synthetic and natural substrates. Herein, we report the use of metal ions from a single element to deposit metal films on various substrates. In a typical metal deposition procedure, Pd2+ ions are anchored on a polycarbonate membrane with vertically aligned pores of 0.6 mu m, which was reduced to its nanoparticles by sodium borohydride. The Pd nanoparticle-modified membrane was then immersed in a Pd plating bath. The Pd2+ ions are reduced by the reducing agent present in the plating bath. The reaction is catalyzed by the Pd nanoparticles. The Pd-modified membrane with vertically aligned Pd tubes were used to convert p-nitrophenol to p-aminophenol, which is an important molecule in the production of acetaminophen. While filtering the reactants through the Pd tubes, due to increased collision between the reactants and the catalyst Pd tubes, 100% conversion is achieved within 5 min. On the contrary, the conversion is only 10% if the membrane is placed in a vessel comprising the reactants. Due to the versatile nature of the metal deposition procedure, nickel was deposited on cotton substrates by a similar procedure. The nickel film-coated cotton cloth showed an impressive electromagnetic shielding interference efficiency of -60 dB while the uncoated cotton cloth did not shield electromagnetic radiation. To demonstrate the versatility of the approach, Pd-coated synthetic polymeric substrates are used to electroadhere gels and gel-like substances. Nickel-coated substrates are not suitable for electroadhesion; hence, a conjugated polymer was deposited on the substrate to electroadhere gel-like substances.

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide